The Volatile Compound Profiles of Fire-Cured and Fermented Na-Oogst Tobacco Leaves (Nicotiana tabacum L.) and Its In-Silico Study - Oktavianawati, Ika; Wulandari, Ulfa; Winata, I Nyoman Adi; Ridho, Atok Ainur; Kedang, Yohana Ivana; Fauziah, Dina Trianggaluh; Yusro, Fatimah (Department of Chemistry, Faculty of Mathematics and Natural Sciences, University of Jember, 2025)
Na-Oogst tobacco is one of the local commodities of Jember, which has been widely used as a raw material for making cigarettes. Product diversification in processing tobacco leaves is very necessary to reduce the danger caused by cigarette consumption. It is also an effort to empower and save the economy of tobacco farmers. Tobacco leaf’ essential oil could be an alternative in maintaining tobacco production. The purpose of this study is to determine the profile (yield and chemical compounds) of Na-Oogst tobacco leaf essential oil content in pre- and post-fermentation. Extraction of essential oils is carried out by two methods, i.e., steam distillation and maceration. The results showed that the extraction from the maceration method produced higher yields than from steam distillation, while the extract from tobacco leaves before fermentation was lower than that after fermentation. The major identified compounds found in tobacco leaves from GC-MS analysis are neophytadiene, nicotine, ledol, phytol, and solanone. Neophytadiene is suggested as a marker compound in tobacco leaf since it is present in all extracts and essential oils in significant amounts, about 23.72-67.37% of the total identified compounds. Further molecular docking of neophytadiene against the D2 dopamine receptor is also investigated in this study.